Non-Inversion Factor VIII Mutations in 80 Hemophilia A Families Including 24 with Alloimmune Responses - Liu, Miao-Liang; Nakaya, Shelley; Thompson, Arthur R. (Thrombosis and Haemostasis, 2002)
Heteroduplex screening identified 74 small mutations in the factor VIII genes of 72 families with hemophilia A. In addition, patients from 3 families with high titer inhibitors had partial gene deletions and 5 unrelated families that were negative for heteroduplex formation had a mutation on direct sequencing. The latter had mild hemophilia A with an inhibitor, and sequencing their exon 23 fragments found a transition predicting a recurrent Arg2150 to His. Of 69 distinct mutations (including the 3 partial gene deletions), 47 are novel. Of small mutations, 51 were missense (one possibly a normal variant and two that could also alter splicing) at 39 sites, 13 were small deletions or insertions (3 inframe and one a normal variant in an intron), 13 were nonsense at 12 sites and 2 altered intron splice junctions. In 24 families, at least one affected member had evidence for an alloimmune response to factor VIII; of these, 11 were associated with missense mutations. In 14 families, de novo origin was demonstrated.
Keywords: Hemophilia A; factor VIII; mutations; inhibitors